2021
DOI: 10.1007/s40279-020-01424-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Contra-Lateral Secondary Anterior Cruciate Ligament Injury: A Systematic Review with Meta-Analysis

Abstract: Background The risk of sustaining a contra-lateral anterior cruciate ligament (C-ACL) injury after primary unilateral ACL injury is high. C-ACL injury often contributes to a further decline in function and quality of life, including failure to return to sport. There is, however, very limited knowledge about which risk factors that contribute to C-ACL injury. Objective To systematically review instrinsic risk factors for sustaining a C-ACL injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 122 publications
4
23
3
1
Order By: Relevance
“…CI confidence interval, M-H Mantel-Haenszel 24, 25] out of the nine used in their analysis were a part of one cohort [19] and the same participants were therefore included multiple times. Our results showed that the impact of family history on CACL injury (OR 2.28) was slightly greater than that reported by Cronström et al [33]. We are not aware of any other review that has combined data on the risk of family history for a primary ACL injury or graft rupture with which to compare the current results.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…CI confidence interval, M-H Mantel-Haenszel 24, 25] out of the nine used in their analysis were a part of one cohort [19] and the same participants were therefore included multiple times. Our results showed that the impact of family history on CACL injury (OR 2.28) was slightly greater than that reported by Cronström et al [33]. We are not aware of any other review that has combined data on the risk of family history for a primary ACL injury or graft rupture with which to compare the current results.…”
Section: Discussioncontrasting
confidence: 65%
“…This review thoroughly investigated family history as a risk factor in relation to primary ACL injuries, graft ruptures and CACL injuries together. A recently published systematic review and meta-analysis of risk factors in CACL injuries by Cronström et al [33] also found those with a family history were at increased risk and reported an OR of 2.07 (95% CI 1.54-2.80, p < 0.001). However, three studies [15,Fig. Odds of sustaining a primary anterior cruciate ligament injury in male individuals compared to female individuals in those with a family history.…”
Section: Discussionmentioning
confidence: 92%
“…Further, as we reported in a recent systematic review, RTS is the risk factor with the strongest association with sustaining a secondary injury to the ACL of the contralateral leg (C-ACL). Notably, athletes who returned to a high activity level (International Knee Documentation Committee [IKDC] questionnaire, level 1–2) or sports including cutting and pivoting were more likely to sustain a C-ACL injury than those who did not return at all or returned to a lower activity level (odds ratio [OR] 3.3) [ 12 ]. Other risk factors for future C-ACL injuries included female sex, age 18 years or younger, family history of ACL injury, and early (≤ 3 months) primary ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“… 41 , 42 , 47 , 49 , 53 , 82–85 Furthermore, returning to a high level of activity post-reconstruction is a risk factor for contralateral ACL injury. 83 In a study of 2,488 primary ACLR from the MOON cohort, Kaeding et al 53 reported that the odds of a contralateral ACL tear increased by 0.12 for every increased point on the Marx activity score.…”
Section: Discussionmentioning
confidence: 99%